Administração pública digital: estudo sobre a constitucionalidade da implementação da blockchain pelo Instituto Nacional da Propriedade Industrial - Lima, Thaisi Leal Mesquita de (2020)
The technological changes that have taken place in the last decades have affected public and private relations and routines, so the State has not been able to do so. The effects of the administration pity the inefficiency and their lack of pace with the current world and social scenario culminating in the constitutional provision distribution. Among these bodies, there is the National Institute of Industrial Property, the federal authority responsible for p. for the development and economic and technological aspects of Brazil, but which does not have sufficient technological infrastructure to deal with the demand it receives, which has led to a waiting period of about eight to ten years for about eight to ten years for the inefficiency noted. and the lack of transparency of this body, which is part of the Brazilian public administration, it is of utmost importance to ascertain whether the performance of the INPI, in its current status, is sufficient to materialize the constitutional standards and provisions to which efficient management is submitted, in order to find in other areas solutions to this problem, not only technical-informational, but also legal. In this context, this work aims to analyze the constitutionality of the use of blockchain technology in the administrative and procedural routine of INPI, as well as to define the concepts of digital public administration, transparency 2.0 and blockchain, which are essential for the development of this study. To this end, bibliographic research was carried out, analysis of reports from international organizations, as well as research on the constitutional and legal provisions that touch the theme, in order to understand what is the basis of traditional public administration and what are the needs and limits that involve the possible change. It is, therefore, research with a qualitative approach, while it intended to describe and analyze data and information. Descriptive and explanatory, as it aimed to analyze the state of the art of the INPI as part of the public administration, explained which factors lead to the current situation of the processes for granting industrial property rights, and concluded whether there is constitutionality and feasibility in changing information and technological infrastructure the autarchy. As for the procedures, this study used mainly bibliographic research and case study, while it was based on fundamentals of books, scientific articles, reports and legislation, as well as developed a case study both about the INPI and about the paradigm cases of use of blockchain in public administration, such as Agenda Teresina 2030, BNDES Token, TruBudget and Junta Comercial do Ceará. Finally, it can be seen that the implementation of a digital public administration is urgent and necessary, as it will contribute to the realization of constitutional principles, such as efficiency, in addition to enabling the effectiveness of transparency 2.0, which will allow citizens to appropriate public information, so that they will become active subjects and contributors to participatory management.